DOSIS OPTIMUM BIJI KELOR (Moringa seed) DALAM MENURUNKAN KEKERUHAN (Turbidity) AIR SUNGAI BETAPUS DI KELURAHAN SEMPAJA UTARA KOTA SAMARINDA - Marjan Wahyuni (jurnal ilmiah manuntung sekolah tinggi ilmu kesehatan samarinda, 2015)
Water is used as daily necessities which must meet the standards of raw water for drinking water, household, and other – other. As in the waters of the North Sempaja Betapus Sub District of North Samarinda territory that location is dihulu Karangmumus River. Physically the water is cloudy, colored and contains organic / inorganic. The aim of this study was to determine the optimum dose of moringa seed in reducing turbidity (Turbidity) Water Betapus River in the Village of North Sempaja Samarinda.This research is a quasi-experimental (Quasi Experiment) or the design of a series of time (Time Series Design) which make measurements before and after affixing moringa seeds with sampling methods Grab Sample for 1 day. This experiment uses a method to purify raw water Jartest Betapus River by adding powdered moringa seeds (Moringan oleifera) into 1 liter of water by varying the dose of 0.5 g / L, 1.0 g / L, 1.5 g / L, and 2.0 g / L. Results of research conducted on Betapus River water showed that the level of turbidity (Turbidity) amounted to 79.1 NTU with a pH of 6.8, so it is said to be ineligible clean water turbidity according Permenkes RI 416 / Menkes / Per / IX / 1990, namely that allowed 25 NTU. After affixing moringa seeds with a variety of different doses, the results showed as follows: the dose of 0.5 g / L = 4.52 NTU; a dose of 1.0 g / L = 7.76 NTU; dose of 1.5 g / L = 9.14 NTU, and a dose of 2.0 g / L = 8.51 NTU. The optimum dose range moringa seeds needed at River raw water Betapus = 0.5 g / L with a percentage of 94.28%. For people who use the river water as the need for clean water for toilets (Bath Wash Case) and so on, you should do a simple treatment with Moringa seed powder according affixing the optimum dose prescribed to reduce levels of turbidity (Turbidity) in water.